Correlations of Chronic Periodontitis with Preeclampsia and Fetal Birth Weight - Octaviana Yoseffin (Indonesian Journal of Obstetrics and Gynecology, 2011)
Objective: Preeclampsia is the main cause of maternal and perinatal mortality and morbidity one of which low birth weight. The cause of preeclampsia is multifactorial, and one of them is infection. High periodontal incidence is found in preeclampsia patients. This study is intended to find correlations between chronic periodontitis with preeclampsia and fetal birth weight. Method: The study was held in RS Dr. Hasan Sadikin Bandung, RSUD Astana Anyar and RSUD Ujung Berung in December 2010 - February 2011 using case-control study design in two groups,with 26 subjects in each group. The subjects were recorded on age, parity, gestational age, diagnosis, fetal birth weight, and periodontal status. Statistical analysis were performed using chi square test and Rank Spearman’s correlation test. Result: The characteristics of study subjects in both groups show no significant difference (p > 0.05). In the preeclampsia group, periodontitis incidence is higher which is 19 (73.08%) compared to control group which is 12 (46.15%). Based on chi square method, there is a significant correlation between periodontitis and preeclampsia with odds ratio value of 3.17 (p = 0.048; p < 0.05; 95%CI (1.19 - 8.41). Based on Rank-Spearman correlation test, there is a moderate negative correlation between periodontitis severity and with fetal birth weight with rs value of = - 0.423 and a p value of 0.002. Conclusion: Chronic periodontitis incidence is higher in preeclampsia group compared to control group. There’s a moderate negative correlation on periodontitis severity with fetal birth weight. The more severe the periodontitis, the lower the fetal birth weight. [Indones J Obstet Gynecol 2011; 35-3: 105-9] Keywords: periodontitis, preeclampsia, fetal birth weight